MicroRNAs as the predictors for atrial fibrillation recurrence after catheter ablation: next-generation sequencing study. (19th May 2022) - Sustr, F; Machackova, T; Pesl, M; Trachtova, K; Svacinova, J; Starek, Z; Spinarova, L; Kianicka, B; Slaby, O; Novak, J
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): This study was supported by Specific research of the Masaryk University (MUNI/A/1156/2021) and Institutional support project of St. Anne's University hospital in Brno. Background: Atrial fibrillation (AF) represents the most common arrhythmia. Catheter ablation (CA) of AF is indicated in patients with recurrent and symptomatic AF episodes fulfilling the criteria stated in the current guidelines. Despite the strict inclusion/exclusion criteria, AF recurrence after CA remains notably high. Thus, identifying a novel marker to more precisely select individuals that will profit from CA would be beneficial. microRNAs, i.e., small non-coding RNAs of the length of approx. 22 nucleotides are known to play crucial roles in the pathophysiology of AF and therefore represent promising biomarkers in the field. Purpose: Aim of the study was to identify potential plasmatic microRNAs as novel biomarkers for predicting AF recurrence after CA. Methods: Prospective monocentric and biomarker-screening study. Altogether 49 consecutive AF patients indicated for CA were enrolled. Before the CA, blood sampling was performed, and plasma was isolated. All patients then underwent CA and were followed up for 6 months. Within the close-up visit at the 6th month, 24-hour ECG Holter monitoring was performed to evaluate participants' rhythm. For the next-generation sequencing (NGS), 5 patients with recurrent AF and 5 age- and BMI-matching patients without recurrent AF were randomly selected from the baseline cohort. NGS was performed using Illumina Instrument, and obtained data were then evaluated using edgeR and DESeq2 algorithms to identify all miRNAs present in the study samples. Filtering was performed to exclude microRNAs with low expression (i.e., base mean value at least 20 and more and expression detectable in all study samples). Comparison of the two groups (with and without AF recurrence) was performed using standard statistical tests with correction for multiple comparisons: differences with log2 fold change above 0, 5 or below -0, 5 with p < 0, 05 were considered biologically and statistically significant. Results: In total, 2069 various microRNAs were identified. Altogether 59 microRNAs statistically significantly differed between the groups. The most altered microRNAs were as follows: miR-29c-5p, miR-183-5p, miR-190b, miR-206, miR-326, miR-505-5p, miR-548b, miR-574-3p, miR-1294 and miR-1296-5p. Conclusion: Using NGS, we have identified 59 potential microRNAs whose plasmatic levels are altered between individuals with and without early AF recurrence. If the results are confirmed on the larger patients' cohort, these microRNAs will represent supportive biomarkers to identify AF patients benefiting from CA.